Tasking planning based on task splitting and merging in relay satellite network - Run-zi LIU; Min SHENG; Cheng-yuan TANG; Jian-dong LI; Kai DU; Yong-an YANG (Tongxin xuebao)
To handle the low planning efficiency of the tasks with too long or too short service time,a task planning scheme was proposed based on task splitting and merging for relay satellite systems.First,a task splitting and merging was developed to transfer the task requirements of user to task units which could be planned with high efficiency.Secondly,based on the parallel machine scheduling model,the optimization problem of the task unit planning to maximize the number of completed tasks in the network was built.Further,a heuristic polynomial time scheduling algorithm was proposed.Simulation results show that compared to the traditional scheme,the task planning scheme perform better in terms of completed task number,resource utilization and fairness.